Feminism's progress : gender politics in British and American literature and television since 1830 - Colatrella, Carol (State University of New York Press, 2023)
"Explores how popular novels, short stories, and television shows from the United States and Britain illustrate the positive effects of feminism and promote gender equity"-- Provided by publisher.
Keywords: Feminism -- History -- 21st century.; Equality.; Women -- Social conditions -- 21st century.; Sex discrimination against women.; Television and women.; Women in literature.; Féminisme -- Histoire -- 21e siècle.; Femmes -- Conditions sociales -- 21e siècle.; Discrimination à l'égard des femmes.; Télévision et femmes.; Femmes dans la littérature.; SOCIAL SCIENCE / Women's Studies.; Equality; Feminism; Sex discrimination against women; Television and women; Women in literature; Women -- Social conditions; History